Vowel Pronunciation of English Words By Filipino Speakers in “Everglow” Short Movie - Melienia, Ingielly (Jurnal DinamikA, 2021)
Language is a way of communication with other people. People can make conversation through a set of words that become a sentence. There is one language that uses as the International language to communicate with other people who come from other countries in this world. Thus, English is used as an intermediate language for communication. One of nations, that use English to communicate, is the Philippines. The research found some phenomena that exist when Filipino speakers speak English. There were two objectives to be analyzed in this study: to find out the English words that the vowel is changing from English vowel into Tagalog vowel and identify the phonological process of Filipino speakers’ pronunciation in the vowel change. The phonological approach is used to solve the problem formulation of the research. The research analyzed a short movie entitled “Everglow” from the Philippines and analyzed the vowel changes in Filipino speakers’ pronunciation. The analysis showed that there were 11 English vowels changes in Filipino speakers’ pronunciation. Furthermore, three phonological processes were found in the vowel change, such as vowel lengthening, vowel raising, and vowel insertion. However, the most phonological process that was usually found in the vowel changes was the vowel lengthening.  Keywords: vowel change, Filipino, phonology.